Grey Forecasting Model Untuk Peramalan Harga Ikan Budidaya - Muhammad Shodiq; Bagus Dwi Saputra (STMIK Budi Darma, 2022)
Price is an important factor to consider because it determines the profit or loss from selling a product. The difficulty of controlling the volatility of fish prices is related to many factors, including stock availability, natural factors, and the level of demand. One way to solve the problem of fish price volatility is to predict fish prices in the future. The purpose of this study is to apply the gray forecasting method to forecasting fish prices, especially in the aquaculture industry. Gray forecasting is a method for creating forecasting models with a small amount of data that provides accurate forecasts. This study uses daily data on prices of Tilapia fish for the period of June 2022 for analysis of gray forecasting calculations. The results show that gray forecasting provides very accurate predictions with aa mafe value of 2.39% of the price of Tilapia fish